Age-related changes in sleep spindles characteristics during daytime recovery following a 25-hour sleep deprivation - Rosinvil, T.; Lafortune, M.; Sekerovic, Z.; Bouchard, M.; Dubé, J.; Latulipe-Loiselle, A.; Martin, N.; Lina, J. M.; Carrier, J. (Frontiers in Human Neuroscience, 2015)
Objectives: The mechanisms underlying sleep spindles (~11-15Hz; >0.5s) help to protect sleep. With age, it becomes increasingly difficult to maintain sleep at a challenging time (e.g. daytime), even after sleep loss. This study compared spindle characteristics during daytime recovery and nocturnal sleep in young and middle-aged adults. In addition, we explored whether spindles characteristics in baseline nocturnal sleep were associated with the ability to maintain sleep during daytime recovery periods in both age groups. Methods: Twenty-nine young (15 women and 14 men; 27.3 ± 5.0) and 31 middle-aged (19 women and 13 men; 51.6 y ± 5.1) healthy subjects participated in a baseline nocturnal sleep and a daytime recovery sleep after 25 hours of sleep deprivation. Spindles were detected on artefact-free NREM sleep epochs. Spindle density (nb/min), amplitude (μV), frequency (Hz) and duration (s) were analyzed on parasagittal (linked-ears) derivations. Results: In young subjects, spindle frequency increased during daytime recovery sleep as compared to baseline nocturnal sleep in all derivations, whereas middle-aged subjects showed spindle frequency enhancement only in the prefrontal derivation. No other significant interaction between age group and sleep condition was observed. Spindle density for all derivations and centro-occipital spindle amplitude decreased whereas prefrontal spindle amplitude increased from baseline to daytime recovery sleep in both age groups. Finally, no significant correlation was found between spindle characteristics during baseline nocturnal sleep and the marked reduction in sleep efficiency during daytime recovery sleep in both young and middle-aged subjects. Conclusion: These results suggest that the interaction between homeostatic and circadian pressure module spindle frequency differently in aging. Spindle characteristics do not seem to be linked with the ability to maintain daytime recovery sleep.